2017
DOI: 10.1242/dev.139303
|View full text |Cite
|
Sign up to set email alerts
|

Enthesis regeneration: a role for Gli1+ progenitor cells

Abstract: The tendon enthesis originates from a specific pool of hedgehogactive Gli1+ progenitor cells that differentiate and produce mineralized fibrocartilage. The current study investigated the regenerative capacity of this cell population by comparing the responses of early postnatal and mature entheses to injury. Lineage tracing studies demonstrated that the original Gli1+ cell population had the capacity to heal immature entheses after injury, but this capacity was lost after the cells differentiated into mature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 26 publications
4
87
0
Order By: Relevance
“…Hedgehog signaling is crucial in endochondral ossification and involved in proper mineralization of the fibrocartilage cells within the enthesis, the tendon to bone insertion site . Gli1 is a transcription factor downstream of Hedgehog signaling .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedgehog signaling is crucial in endochondral ossification and involved in proper mineralization of the fibrocartilage cells within the enthesis, the tendon to bone insertion site . Gli1 is a transcription factor downstream of Hedgehog signaling .…”
Section: Resultsmentioning
confidence: 99%
“…Hedgehog signaling is crucial in endochondral ossification and involved in proper mineralization of the fibrocartilage cells within the enthesis, the tendon to bone insertion site. (40)(41)(42)(43)(44) Gli1 is a transcription factor downstream of Hedgehog signaling. (45,46) To investigate whether Hedgehog signaling activity is involved in Achilles tendon ossification in Mkx -/mice, we crossed mice carrying the Gli1 LacZ knock-in allele with Mkx -/mice and subsequently analyzed LacZ reporter activity in the Mkx -/mutant and control littermates.…”
Section: Inactivation Of Mkx Postnatally and Specifically In Tendon Cmentioning
confidence: 99%
“…Although the majority of rodent rotator cuff studies have been carried out in rat, the mouse shoulder anatomy was recently shown to be comparable to rat and human. The very small size of the mouse rotator cuff precluded its use in earlier studies; however, novel microsurgical techniques have now been applied to successfully create partial and full detachment injuries with surgical repair, thereby opening new avenues for mechanistic research . Despite the numerous advantages of rat models, limitations include scar‐mediated healing (human tears do not undergo spontaneous healing), quadrupedal gait, and small scale relative to human .…”
Section: Rotator Cuff Injury Modelsmentioning
confidence: 99%
“…The very small size of the mouse rotator cuff precluded its use in earlier studies; however, novel microsurgical techniques have now been applied to successfully create partial and full detachment injuries with surgical repair, thereby opening new avenues for mechanistic research. [18][19][20][21][22][23][24] Despite the numerous advantages of rat models, limitations include scar-mediated healing (human tears do not undergo spontaneous healing), quadrupedal gait, and small scale relative to human. 17 While joint replacement or other medical devices cannot be tested in rodent models, preclinical studies testing the efficacy of cell and biomolecule-based therapies are acceptable in rodents for meeting FDA standards.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Collectively, these tissues define an enthesis and function to enact a force to the bone from muscle shortening while dissipating loads optimizing mechanical efficiency (Benjamin et al, 1986;Currey, 2002;Benjamin et al, 2004;Schwartz et al, 2013;Deymier et al, 2017). The micro structure (Sanchez et al, 2013;Beaulieu et al, 2016;Carbone et al, 2016;Cury et al, 2016;Zhao et al, 2017), mineral (Schwartz et al, 2012;Deymier et al, 2017), and protein composition (Cury et al, 2016), as well as the observed molecular signaling (Blitz et al, 2009;Carbone et al, 2016;Killian and Thomopoulos, 2016) and signatures of its cell populations (Zelzer et al, 2014;Schwartz et al, 2015;Schwartz et al, 2017) support the concept of enthesis as a discrete organ (Benjamin et al, 2004) with specific identifiable developmental processes, structure, composition, and function (Zelzer et al, 2014).…”
mentioning
confidence: 99%